The efficiency of judo techniques in the light of amendments to the rules of a sports contest - Adam, M.; Tabakov, S.; Klimowicz, P.; Paczoska, B.; Laskowski, R.; Smaruj, M. (Journal of Combat Sports and Martial Arts, 2012)
In 2009 and 2010 very significant amendments to sports rules of the contest judo were introduced. The aim of these changes was to make judo sport contests more appealing and to eliminate or limit performing technical elements which came from outside the accepted classification of judo techniques. Material and methods. The material consisted of an analysis of fights of men`s judo representatives recorded by audio-visual means during the Olympic Games in 2008, 2012 the World Championships in 2009, 2010, 2011. The fights were converted by means of a graphic method and then analysed. The most efficient teams, dominant techniques, the efficiency of groups of techniques and the scope of administered penalties were determined. Results. In 2008 the most efficient men`s judo team was from Korea, in 2010-2011 from Japan and in 2012 from Russia. In 2008, 2009 and 2012, hand throws were the most efficient techniques and in 2010 and 2011 leg throws. During the 2008 Olympic Games sumi gaeshi was the most dominant throw. In the other competitions (2009-2012) the most dominant throw was seoi nage. Conclusions. In 2010 and 2011, the efficiency of hand techniques has diminished while the efficiency of leg techniques has grown. In 2012 the efficiency of all throwing techniques has declined. The number of points granted for judges` penalties has also fallen.